Neoadjuvant Stereotactic Ablative Radiotherapy in Pancreatic Ductal Adenocarcinoma: A Review of Perioperative and Long-Term Outcomes - Robert Michael O’Connell; Emir Hoti (Diseases)
The incidence of pancreatic ductal adenocarcinoma (PDAC) is continuing to rise globally, while overall survival continues to be poor. Margin-negative (R0) surgical resection is essential to improve patient outcomes. With increasing understanding of the importance of anatomy and biology to establishing the resectability of PDAC, neoadjuvant therapy (NAT) has emerged as an important strategy to achieve an R0 resection, particularly for those with borderline resectable (BR-PDAC) and locally advanced disease (LA-PDAC). However, despite the multiple randomised controlled trials (RCTs) published in recent years, the optimum regime has yet to be fully established. The role of neoadjuvant chemoradiation therapy (CRT) remains controversial, possibly allowing for improved local disease control at a potential cost of interrupting systemic treatment. The emergence of stereotactic ablative radiotherapy (SABR), in place of conventional radiation therapy, improves patient tolerance of NAT and may improve local tumour control for patients with PDAC during limited fractions, minimising systemic therapy interruption. A particular niche for SABR may be as part of NAT for LA-PDAC, potentially converting a minority of patients with favourable biology to allow for resection. While pancreaticoduodenectomy can be technically challenging following NAT, there is no difference in the rate of major morbidity or mortality post operatively. Indeed, post-operative pancreatic fistula (POPF) rates may be lower following NAT. Overall, however, evidence for SABR in a neoadjuvant setting for BR- and LA-PDAC remains sparse.